Applications of Space Technology for Accelerated Infrastructures Development for Rural Areas Development in Nigeria - Onuh, S. O.; Aiyeola, S. Y.; Tofade, C. T.; Adesina, L. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Rural to urban migration still persists in Nigeria despite government’s claim of rural development programs. This situation if not checked portends negative signal for the already over-populated urban areas, particularly in areas of food security, sanitation, housing, crimes, etc. The development of rural areas is measured by the availability of infrastructures and economic opportunities that are available to the people. These infrastructures include: transportation infrastructure, educational infrastructure, healthcare infrastructure, energy infrastructure, water supply/sanitation infrastructure, information and communication technology (ICT) infrastructure and so on. Rural areas in Nigeria urgently require accelerated infrastructure development to alleviate poverty. When this is done rapid growth is ensured and poverty is drastically reduced. The world today has become increasingly reliant on information and communication technologies (ICT) and with it comes the need for societies and communities to stay connected and be integrated into the global information super highway. Space technology today has also become an integral part of global information infrastructure, connecting people across the world and serving communications needs of governments, businesses and individuals. For Nigeria to be technologically developed, the “digital divide” (that is the imbalance between urban and rural dwellers in which the rural dwellers have far lesser access to the same quality of knowledge), information, and education resources that are more readily available to urban areas because of the absence of required communication infrastructure need to be removed. The digital divide brings a virtual, but real impediment to the advancement of the society and individuals in remote rural settlements. This paper seeks to discuss the applications of space technology for accelerated rural infrastructures development in rural areas in Nigeria